Dakwah Radio di Era Media Baru: Reinventing Strategi dan Konten untuk Meningkatkan Jangkauan - Aldin Adama (Research and Community Service UNIVERSITAS KALBIS, 2026)
This article aims to analyze and formulate strategies for reinventing radio dakwah (Islamic propagation) in the face of the new media landscape to enhance its reach and relevance. The method employed is a systematic literature review, examining various scientific literature, journals, and books related to dakwah in new media, digital media trends, audience behavior, and broadcasting media management. The research findings indicate that traditional radio dakwah faces significant challenges from shifting digital audience behavior but holds substantial opportunities through platform convergence. It is found that reinvention strategies must include multi-platform adoption, the development of interactive and visual bite-sized content, and the optimization of data-driven measurement. This article concludes that transforming into a content hub and collaborating with digital influencers are key to creating a more effective and measurable dakwah ecosystem in the new media era, thereby sustaining and expanding its influence amidst intense media competition.